2006
DOI: 10.1097/01.qai.0000209900.05126.25
|View full text |Cite
|
Sign up to set email alerts
|

Trends in HIV Prevalence Among Pregnant Women in Italy, 1994 to 2002

Abstract: The number of children born to an HIV-positive mother calls for continued efforts to prevent vertical transmission of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
1
9
1
Order By: Relevance
“…16 Despite more than 1000 cases, the study sample size did not provide enough power to evaluate associations with specific defects, and CIs for the prevalence of birth defects for some drugs were still relatively wide. Nonetheless, prevalence data are consistent with the main reference sources, and no drugs showed a birth defect rate above 5% for first-trimester exposure.…”
Section: Strength and Weaknessesmentioning
confidence: 99%
“…16 Despite more than 1000 cases, the study sample size did not provide enough power to evaluate associations with specific defects, and CIs for the prevalence of birth defects for some drugs were still relatively wide. Nonetheless, prevalence data are consistent with the main reference sources, and no drugs showed a birth defect rate above 5% for first-trimester exposure.…”
Section: Strength and Weaknessesmentioning
confidence: 99%
“…Our study examined different aspects of treatment and care during pregnancy and provided information on ARV treatment and pregnancy outcomes in a large cohort of HIV‐infected women of different provenance followed in a European country. Recent data on HIV seroprevalence at delivery in Italy indicate an estimated seroprevalence of 0.66 per 1000, corresponding to an estimate of 346 liveborns from HIV‐positive mothers in 2002 11 . Our study and the data provided here, based on about 1000 pregnancies reported in less than 5 years, represent the vast majority of the pregnancies occurring in HIV‐positive women in Italy, with a nationwide distribution of participating centres.…”
Section: Discussionmentioning
confidence: 57%
“…This is an ongoing observational study established in Italy in 2001, which covers, based on available prevalence data [6], roughly 30–40% of live births from women with HIV in Italy. Site participation is voluntary, and at present is based on more than 30 clinicians reporting from Obstetrics, Infectious Diseases, and Paediatrics departments across the country.…”
Section: Methodsmentioning
confidence: 99%